2021
DOI: 10.1002/jbt.22847
|View full text |Cite
|
Sign up to set email alerts
|

The effects of edaravone, a free‐radical scavenger in lung injury induced by valproic acid demonstrated via different biochemical parameters

Abstract: In this study, we aimed to evaluate whether edaravone (EDA) has a protective role against valproic acid (VPA)-induced lung damage via its antioxidative activity. Male Sprague-Dawley rats were split into four groups. Control (n = 8) rats; rats given EDA (30 mg kg −1 day −1 ; n = 10); rats given only (VPA, 500 mg kg −1 day −1 ; n = 10); rats given VPA + EDA (in the same dose and time) for 7 days. EDA and VPA were applied intraperitoneally. After 8 days, lung tissues were immediately taken from the rats. In lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…It was shown that TOS levels remarkably increased whereas TAS levels notably decreased in children with seizures taking sixty days on VPA monotherapy [29]. Present findings are line with our recent article [30]. In the present study, administration of edaravone to VPA given rats resulted in decreased ROS, TOS, and OSI levels and increased TAS levels.…”
Section: Discussionsupporting
confidence: 92%
“…It was shown that TOS levels remarkably increased whereas TAS levels notably decreased in children with seizures taking sixty days on VPA monotherapy [29]. Present findings are line with our recent article [30]. In the present study, administration of edaravone to VPA given rats resulted in decreased ROS, TOS, and OSI levels and increased TAS levels.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, ALA has been described as being involved in the most important energy production pathway, the Krebs cycle, where ALA plays a vital role as a coenzyme assisting in the transfer of acyl groups (15). Its protective effects on different systems of VPA and α-cypermethrin have been reported by many researchers, respectively (7,16,17).…”
Section: Introductionmentioning
confidence: 92%
“…Despite its protective and preventive effects, VPA has been declared to have many serious side effects and this drug has taken the lead in the formation and construction of free radical species which damage many tissues and organs like heart, lung, liver, brain, testis, etc. (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The preparates were centrifuged at +4 °C and 10000 x g for 10 minutes. The supernatants were collected for determining biochemical parameters as described previously in our study [8][9][10] ; reduced glutathione (GSH), lipid peroxidation (LPO), advanced oxidized protein products (AOPP), hydroxy proline (HP), catalase (CAT), carbonic anhydrase (CA), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-S-transferase (GST), total antioxidant capacity (TAC), total oxidant status (TOS), reactive oxygen species (ROS), oxidative stress index (OSI), nitric oxide (NO), xanthine oxidase (XO), lactate dehydrogenase (LDH) superoxide dismutase (SOD), paraoxonase (PON) and lung protein levels were determined. Histological Analyses: F or light microscopic investigations, after fixing in 10% neutral buffered formaldehyde, lung samples were processed routinely before embedding in paraffin.…”
Section: Preparation Of White Cabbage Aqueous Extract (Wcae)mentioning
confidence: 99%